Efficacy and safety of a new non-pesticide lice removal product. - Scanni, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
This report is aimed at verifying in an open "in vivo" study efficacy and safety of a new lice removal product (Paranix ®, Chefaro Pharma Italy). The latter is a non-pesticide spray consisting of active natural agents, particularly coconut oil extract, anise essential oil and Ylang ylang oil. The efficacy and safety of Paranix® was compared to those ones of malathion (Aftir® gel, Biochimici PSN Italy) in 24 subjects, whose age ranged between 4 and 15 years. The latter were randomly treated with one of the two products. No subject showed clinically evident side effects attributable to the used product. 11/12 subjects of both groups did not show live lice or nits when combed four days after the first treatment. Two subjects in the group treated with Aftir and one subject in the group treated with Paranix complained about the odor of the product. In conclusion Paranix proved as effective as the strong lice removal product of the control group and devoid of side effects.